The Influence of Mastery of Simple Past Tense and Adverbs on Recount Text Writing Skills of Vocational High School Students in Bogor Regency - Ropitasari, Anna; Wahyudin, Dinn; Karim, Abdul; Dewi, Maftuhah; Rosyad, Ramlan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
English grammar mastery is very important for Vocational High School (SMK) students, especially in writing recount texts, where the use of simple past tense and adverbs is very important. However, many students have difficulty with these elements, which affects their writing skills. This study aims to investigate the combined effect of simple past tense and adverb mastery on students' ability to write recount texts effectively. A quantitative research design with a correlational approach was used, involving 60 students from 30 Vocational High Schools in Bogor Regency. Data were collected through grammar tests and writing tests, focusing on students' mastery of simple past tense and adverbs. Data analysis was carried out using SPSS version 25.0, including normality, linearity, and regression tests. The results showed that simple past tense mastery contributed 17.86%, while adverb mastery contributed 27.19% to the variance of students' writing skills. The combined effect of the two variables explained 45.1% of the variance of students' ability in writing recount texts. These findings emphasize the importance of teaching simple past tense and adverb usage in improving students’ writing ability. The implications of this study suggest that English curriculum in Vocational High Schools should prioritize these areas to improve students’ ability to communicate effectively in writing.